Gambaran Komitmen Organisasi pada Mahasiswa yang Aktif di Lembaga Kemahasiswaan, Pekerjaan Paruh Waktu, dan Perkuliahan - Rosa Dyah Anggraini; Rudangta Arianti (Universitas Kristen Maranatha, 2019)
This study aims to see a picture of commitment to students who are active in three main areas, namely lectures, student organizations, and part-time work. Although experience and success in all three can increase the chances of success in the world of work, but very few students are able to live it simultaneously well. The method used was a case study involving one male and one female participant. The results showed that affective, normative, and continuity commitment contributed to the loyalty and performance of both participants in the three areas. Their commitment is also influenced by the goals to be achieved, priority goals, perceptions of leadership and support from colleagues in the team. Keywords: organizational commitment, student organizations, work part time